2017
DOI: 10.1103/physreve.96.022122
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Anderson localization in certain random lattices

Abstract: We report on the transition between an Anderson localized regime and a conductive regime in a 1D scattering system with correlated disorder. We show experimentally that when long-range correlations are introduced, in the form of a power-law spectral density with power larger than 2, the localization length becomes much bigger than the sample size and the transmission peaks typical of an Anderson localized system merge into a pass band. As other forms of long-range correlations are known to have the opposite ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11] Though the basic origin of Anderson localization, which is the interference of wave components multiply scattered by randomly placed scattering centers, is wellunderstood, new and surprising aspects of the phenomenon have been discovered continually. [12][13][14][15][16][17][18][19][20] Differences in the types of wave equations, the material properties and the nature of disorder all affect Anderson localization strongly and can cause conceptually new phenomena to occur. Recently, much interest has been paid to the localization arising in new kinds of condensed-matter materials and artificially fabricated metamaterials.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Though the basic origin of Anderson localization, which is the interference of wave components multiply scattered by randomly placed scattering centers, is wellunderstood, new and surprising aspects of the phenomenon have been discovered continually. [12][13][14][15][16][17][18][19][20] Differences in the types of wave equations, the material properties and the nature of disorder all affect Anderson localization strongly and can cause conceptually new phenomena to occur. Recently, much interest has been paid to the localization arising in new kinds of condensed-matter materials and artificially fabricated metamaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Email address: nguyenbaphi@muce.edu.vn https//doi.org / 10.25073/2588-1124/vnumap.4498 During the recent few decades, the influence of spatially correlated disorder on the wave propagation and localization properties has been attracted much attention from theoretical as well as experimental researchers [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. It has been demonstrated that some special kinds of short-range correlated disorder can produce delocalized eigenstates even in one dimension [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been much interest in the roles of short-range and long-range disorder correlations in localization phenomena [33,[44][45][46]. In this paper, we extend this approach to the localization in Dirac systems.…”
Section: Introductionmentioning
confidence: 99%